384 Motives for kratom self-medication: contents of public comments solicited by the FDA. (April 2022) - Tobacyk, Julia; Parks, Brian; Brents, Lisa
Abstract : OBJECTIVES/GOALS: The present study sought to investigate kratom use motives among the U.S population with the goal of discovering previously unknown health-related reasons for kratom use by the general public. METHODS/STUDY POPULATION: To guide decisions regarding kratom regulation, the FDA solicited comments from the public regarding the abuse potential of these substances, medical usefulness, and impact of scheduling changes from July 2021 until August 2021. Comment participation was open to the public. The first 6, 353 consecutive comments posted on the Federal Register website were retrieved and analyzed. Duplicate comments and comments not pertaining to kratom were excluded from the analysis. The comment submissions were reviewed and categorized using an inductive approach via thematic content analysis. RESULTS/ANTICIPATED RESULTS: Respondents reported over 108 independent health-related reasons for kratom self-medication. Most often fell under the categories of mental health (1911 counts), pain management (1873 counts), substance use disorder (1635 counts), rheumatic diseases (613 counts), and degenerative spine diseases (247 counts). Many comments (701 counts) reported use for miscellaneous purposes, which included to increase focus (212 counts), treat insomnia (127 counts), and decrease fatigue (99 counts). Neurological diseases (e.g., migraines, restless legs syndrome, and multiple sclerosis) and digestive disorders (e.g., irritable bowel syndrome and Crohns Disease) were also reported (147 and 96 counts, respectively). Respondents also reported on the abuse potential and adverse effects of Kratom (122 counts). DISCUSSION/SIGNIFICANCE: This is the first study to delineate and classify motives for kratom use among Americans. Individuals reported using kratom for a wide spectrum of health-related reasons. Though these results may be influenced by the placebo effect, they suggest that kratom alkaloids may possess therapeutic activity for previously unknown applications.